ROLE AND IMPORTANCE OF AGROLOGISTICS IN THE “SUPPLY CHAIN” OF ORGANIC AGRICULTURAL PRODUCTS - Amirkulov, Shukhrat Olimovich (THE INNOVATION ECONOMY, 2024)
The article highlights the role and importance of the agrologistics system in the sales chain of organic agricultural products.